The Psychology of Music 2013
DOI: 10.1016/b978-0-12-381460-9.00012-2
|View full text |Cite
|
Sign up to set email alerts
|

Music and Cognitive Abilities

Abstract: ABSTRACT-Does music make you smarter? Music listening and music lessons have been claimed to confer intellectual advantages. Any association between music and intellectual functioning would be notable only if the benefits apply reliably to nonmusical abilities and if music is unique in producing the effects. The available evidence indicates that music listening leads to enhanced performance on a variety of cognitive tests, but that such effects are shortterm and stem from the impact of music on arousal level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
171
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(195 citation statements)
references
References 279 publications
18
171
0
6
Order By: Relevance
“…Therefore, listening to pleasant music appears to be beneficial for reducing neglect behaviours in real-world situations. The underlying mechanism for the participants' improvement while listening to pleasant music may be their increased arousal and positive mood, as proposed by the arousal-and-mood hypothesis [5,6]. VAS measures showed that patients gave themselves significantly higher scores on mood and arousal levels when they listened to pleasant music but not when listening to unpleasant music or white noise.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, listening to pleasant music appears to be beneficial for reducing neglect behaviours in real-world situations. The underlying mechanism for the participants' improvement while listening to pleasant music may be their increased arousal and positive mood, as proposed by the arousal-and-mood hypothesis [5,6]. VAS measures showed that patients gave themselves significantly higher scores on mood and arousal levels when they listened to pleasant music but not when listening to unpleasant music or white noise.…”
Section: Discussionmentioning
confidence: 97%
“…Research has shown that music improves a variety of cognitive functions in healthy people [4,5]. According to the arousal-and-mood hypothesis, music is a stimulus that influences the individual's arousal level and mood, which can consequently affect cognitive performance, including attention [5][6][7][8]. It has been suggested [9] that, because of right parietal and frontal region lesions, patients with unilateral neglect may have a deficit in maintaining generalized vigilance, which is often associated with impaired leftward exploration of space.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to cognitive abilities, listening to music has been shown to have beneficial short-term effects such as superior spatial abilities in participants listening to classical music compared to participants in a silent condition and participants who received relaxation instructions (Rauscher, Shaw & Ky, 1993). Long lasting effects have also been reported, for instance from childhood music lessons (Schellenberg, 2005). …”
mentioning
confidence: 99%
“…While most studies show that listening to instrumental and vocal music impairs performance of a cognitive task (Alley & Greene, 2008;Avila, Furnham, & McClelland, 2012;Cassidy & MacDonald, 2007;Furnham & Bradley, 1997;Salame & Baddeley, 1982;Smith, 1985;Stroupe, 2005), a few studies suggest that background music does not interfere with performance. For example, teenagers and college students have expressed lower levels of concentration and higher levels of distraction during academic assignments while listening to certain kinds of music (Jones, 2010;Schellenberg & Weiss, 2013). Similarly, background music has been found to have a negative impact on productivity in some workplaces (Uhrbrock, 1961).…”
Section: State Of the Artmentioning
confidence: 99%
“…A recent extensive review of music and cognitive abilities by Schellenberg and Weiss (2013) concluded that the effect is dependent on numerous factors. These factors range from the type of cognitive task, context, choice of background music, tempo, intensity, and presence or absence of vocals, to individual differences.…”
Section: Chapter 2 Literature Review the Effect Of Background Music mentioning
confidence: 99%